The General Ordinances of the City of Charleston, South Carolina 199–200 (1895) - (:unkn) unknown (My University, 1815)
ch. 15, §§ 566-570: Sec. 566.[1] It shall not be lawful for any person or persons to carry gunpowder without a secure and proper covering, in any wagon, cart, dray, or otherwise, through the streets, lanes, or on the wharves of this City, and any person or persons so offending, shall forfeit, for every such offence, the sum of fifty dollars. Sec. 567.[2] It shall not be lawful for any person or persons to sell any gunpowder, which may at the time be within the City of Charleston, in any quantity, without having first obtained a license to keep and sell gunpowder, the said license to be issued by the Clerk of Council, who shall receive, for the use of the City, from the person obtaining the license, the sum of one dollar for each license so issued, and every such license shall be in force for one year from the date thereof, unless previously annulled by the City Council, and no longer; and every person or persons offending herein shall forfeit and pay for the said offence the sum of one hundred dollars. Sec. 568.[3] It shall not be lawful for any merchant, factor, retailer, or dealer in gunpowder, or any person or persons whomsoever, to retain, have, or keep in his, her, or their possession, any quantity of gunpowder exceeding one pound in weight, unless the same shall be well secured in a tin canister or canisters, which said canisters shall be plainly marked or labelled on the outside thereof, with the word “Gunpowder,” and shall be deposited and kept on the right side of the principal door or entrance to the store, shop, or premises wherein the same may be; and any person or persons offending against any of the provisions of this section, shall forfeit and pay, for every such offence, the sum of one hundred dollars. Sec. 569.[4] No merchant, factor, retailer, or dealer in gunpowder, or any person or persons whomsoever, within this City, shall retain, keep, or have, in his, her or their possession, at any one time, a greater quantity of gunpowder, than twenty-five pounds weight; and, on information given to the Mayor, or the same coming by any means, to his knowledge, of a greater quantity than twenty-five pounds weight, in the possession of, or within the enclosure or enclosures of any person or persons whomsoever, the Mayor is hereby required and directed to prosecute such person or persons so offending, in any court of competent jurisdiction, when, on conviction of the same, the party shall be fined in the sum of one hundred dollars. Sec. 570.[5] It shall not be lawful to establish or keep within the limits of the City, any magazine, or place for the storage of gunpowder, nor to keep any gunpowder in any place within the said limits, excepting in small quantities, as herein provided, under a penalty or fine not exceeding five hundred dollars
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER